Review on MXenes-Based Electrocatalysts for High-Energy-Density Lithium–Sulfur Batteries - Zuo, Xintao; Qiu, Yanhui; Zhen, Mengmeng; Liu, Dapeng; Zhang, Yu (Nano-Micro Letters, 2025)
Lithium–sulfur batteries (LSBs) hold significant promise as advanced energy storage systems due to their high energy density, low cost, and environmental advantages. However, despite recent advancements, their practical energy density still falls short of the levels required for commercial viability. The energy density is critically dependent on both sulfur loading and the amount of electrolyte used. High-sulfur loading coupled with lean electrolyte conditions presents several challenges, including the insulating nature of sulfur and Li2S, insufficient electrolyte absorption, degradation of the cathode structure, severe lithium polysulfide shuttling, slow redox reaction kinetics, and instability of the Li metal anode. MXenes-based materials, with their metallic conductivity, large polar surfaces, and abundant active sites, have been identified as promising electrocatalysts to improve the redox reactions in LSBs. This review focuses on the significance and challenges associated with high-sulfur loading and lean electrolytes in LSBs, highlighting recent advancements in MXenes-based electrocatalysts aimed at optimizing sulfur cathodes and lithium anodes. It provides a comprehensive discussion on MXenes as both active materials and substrates in LSBs, with the goal of enhancing understanding of the regulatory mechanisms that govern sulfur conversion reactions and lithium plating/stripping behavior. Finally, the review explores future opportunities for MXenes-based electrocatalysts, paving the way for the practical application of LSBs. Highlights: 1 The significance and challenges associated with high-sulfur loading and lean electrolytes in lithium–sulfur batteries are comprehensively reviewed. 2 Catalytic properties of MXenes-based electrocatalysts are optimized via d-band center tuning, internal electric field constructing, single-atom seeding, and cocktail effects introducing. 3 The structure–activity relationships between MXenes-based electrocatalysts and lithium–sulfur battery performances are comprehensively summarized.